Minangkabau Traditional Music Practice Learning Strategies; Student Competency Achievement In The Impact Of Pandemic - Hengki Armez Hidayat; Syeilendra Syeilendra; Marzam Marzam; Uswatul Hakim (Gondang: Jurnal Seni dan Budaya, 2023)
Education is one sector that plays an important role in building the nation and forming a complete human being. The impact of the pandemic condition makes the learning process at all levels of school to college feel very less enthusiastic. This is because the teaching and learning process which was initially carried out directly / face to face shifted to the learning and teaching process which was carried out through platforms that were integrated into internet-based networks (e-learning). The purpose of this study was to find and design a learning strategy for the Minangkabau Traditional Music Practice Course, FBS UNP Sendratasik Department. From the situation and conditions seen through the GAP analysis, several techniques/procedures must be passed so that the learning objectives can be achieved. The research method was carried out through several stages, including; 1) observation, 2) design of learning devices, 3) implementation of learning, and 4) tests, evaluations and revisions. This research is proven through stages; 1) learn the basic principles of the technology under study, 2) use the formulation of technology concepts; and 3) proof-of-concept of important functions and/or characteristics analytically and experimentally regarding learning strategies for Minangkabau Traditional Music Practice to achieve student competence.